Workforce requirements for comprehensive ischaemic stroke care in a developing country: the case of Saudi Arabia - Fahmi Al-Senani; Mohammad Salawati; Mohammed AlJohani; Matthieu Cuche; Valeska Seguel Ravest; Simon Eggington (BMC, 2019)
Abstract Background Ischaemic stroke care requires a co-ordinated multi-disciplinary approach to optimise patient outcomes. Current care provision in Saudi Arabia is below international recommendations, and with increasing patient numbers, variable access to new therapies, and sub-optimal co-ordination of staff, the Kingdom's Ministry of Health has prioritised strategies to develop stroke care. Our objective was to use local epidemiological data to predict stroke incidence and to combine this with international staffing recommendations to estimate future staff requirements and their costs over a 10-year period. Methods We researched existing stroke services and staff availability within Saudi Arabia to establish current provision, undertook epidemiological modelling to predict stroke incidence, and used international staffing recommendations for acute and rehabilitation services to develop a care pathway to provide state-of-the-art stroke services. This information was used to determine the additional staff requirements, and their costs, across the Kingdom. Results Our research concluded that current staff numbers and services are inadequate to cope with the projected increase in the number of stroke cases. In order to provide acute and rehabilitation services which use the latest technologies, re-organisation of existing staff and services would be required, together with significant investment in new staff across several disciplines. An estimated additional 43.8 full-time equivalent stroke neurologists would be required, plus 53.5 full-time equivalent interventional neuroradiologists in addition to expansion of occupational therapy and psychology services. The total cost of additional staff over 10 years was estimated to be 862 390 778 Saudi Riyals ($229 970 874). Conclusions Providing high-quality care for ischaemic stroke patients would involve significant investment in new staff in Saudi Arabia. Further research is required on the applicability of international staffing ratios to countries where there is a significant workforce gap. Nevertheless, this analysis provides a framework to inform stroke care planning and can be adapted to other regions or countries.